Neutralization of the lethal activity from bothrops atrox venom by hyperimune llama serum (Lama glama) [Neutralización de la actividad letal del veneno de serpiente bothrops atrox por suero hiperinmune de llama (Lama glama)] - Calderon H.B. (2020)
Objectives: To evaluate the capacity of the hyperimmune llama serum (Lama glama) to neutralize the lethal activity of Bothrops atrox venom in laboratory mice. Materials and methods: Mean lethal dose (LD50 ) was calculated from a Bothrops atrox venom sample pool from Peru. The antibody titers were measured by ELISA assay; and the immune serum neutralization potency was measured by calculating the mean effective dose (ED50) during the immunization period. Results: The venom’s LD50 was 3.96 ?g/g; similar to what was found in other studies about Bothrops atrox carried out in Peru. The titers of antibodies against the venom increased rapidly in the llama, demonstrating a fast immune response; however, the neutralization capacity increased slowly and required several doses and immunization reinforcements, obtaining a ED50 of 3.30 ?L/g mouse and a neutralization potency of 3.6 mg/mL after 15 immunizations. Conclusions: The hyperimmune llama serum is able to neutralize the lethality of the Bothrops atrox venom from Peru in laboratory mice.